Green Economy and Digital Marketing-Based Financial Management for MSMEs in Lampung - Rindu Rika Gamayuni; Einde Evana; Fajar Gustiawaty Dewi; Fitra Dharma; Anggun Trisnani (Indonesian Journal of Community Engagement, 2025)
This community service activity disseminates the research results of the project leader and is aimed at MSME partners in Lampung Province engaged in various business sectors, including handicrafts, snacks, culinary products, beverages, coffee, tapis, batik, and fashion. Green Economy-based financial management refers to a financial management concept that integrates environmental sustainability as a key component in achieving the Sustainable Development Goals (SDGs). Based on situation analysis and an initial survey, the main problems faced by MSMEs were identified as: (1) weak financial management, (2) limited product marketing through digital platforms, and (3) inadequate production waste management. The implementation method included situation analysis, capacity building through knowledge sharing and training, as well as monitoring and evaluation activities. The results of this program showed: (1) improved knowledge and understanding among participants regarding environmentally friendly financial management practices, (2) enhanced ability of MSMEs to market products through digital marketing, thereby increasing income and business continuity, and (3) better waste management practices using the 3R approach (reduce, reuse, recycle) to create value-added products. Overall, this activity has made a significant practical contribution by strengthening MSMEs’ capacity to apply sustainable financial management and digital marketing strategies that support long-term business resilience and environmental sustainability.